Germany-Iran Relations in Political-Military Sphere: The Impossible Unlocking of Potential? - V. S. Мirzekhanov; Ph. O. Trunov (Vestnik MGIMO-Universiteta)
The article explores the current relations between Germany and Iran in politicalmilitary sphere. Both countries belong to the category of emerging powers (the Germany is perhaps the single emerging power among Euro-Atlantic states). Outlining the contours of bilateral relations, the authors underline the presence of imperial historical code in each country, the growing internal political problems (dwindling authority of the ruling elites) and mutual interest in deepening trade-industrial partnership with Germany becoming a technological modernizer of Iranian economy.The authors show that Iranian factor has a growing impact over German policy in the Near East and the Middle East, especially in Lebanese, Syrian, Iraqi and Yemeni armed conflicts. In the first three cases Germany tries to limit the scale, the character (non-combatant capabilities), geographic area (not in deep regions) of the Bundeswehr usage. One of the key reasons of it is that Germany avoids being drawn into action against the Iranian troops or its junior allies («Hezbollah» in Lebanon, Shia combatants in Southern Iraq). Germany also recognizes that ignoring Iranian interests in each of these cases will make it difficult to maintain its political-military presence in the region. Because of the Yemen conflict with active participation of Saudi Arabia Germany has imposed arms embargo for the Kingdom.Germany attempted to keep the Iranian nuclear deal after Trump`s administration withdrawal from the agreement. The authors try to estimate the probable position of Germany towards possible military-political crisis in the region involving Iran and especially towards a potential US war against Iran.What result will Germany strive for in the Iranian direction? According to the authors, this is a significantly expanded formula of 2015. In addition to maintaining the JCPOA and mutually beneficial growth in trade and economic cooperation, this formula includes:– minimizing the threat of a military conflict against Iran (which has become especially important after the assassination of General Qasem Soleimani on January 3, 2020);– in exchange for this clear limitation of Iran’s influence in Lebanon, Syria, Iraq and Yemen.